Effect of changes in children's bedtime and sleep period on targeted eating behaviors and timing of caloric intake. (April 2022) - Hart, Chantelle N.; Spaeth, Andrea M.; Egleston, Brian L.; Carskadon, Mary A.; Raynor, Hollie A.; Jelalian, Elissa; Owens, Judith A.; Considine, Robert V.; Wing, Rena R.
Abstract: Short sleep is associated with obesity risk. Experimental studies with adults and observational studies with children demonstrate that changes in eating, including increased caloric intake from energy-dense foods and sugar-sweetened beverages as well as increased caloric intake in the evening, may partially account for this increased risk. We therefore examined whether experimental changes in children's sleep period lead to changes in reported caloric intake from energy-dense snack foods and sugar-sweetened beverages, and in the evening. Thirty-seven children, 8–11 years old, completed a three-week study that used a within-subject randomized cross-over design. Children slept their typical amount for one week and were subsequently randomized to either increase or decrease their typical amount by 1.5 h/night for one week; the alternate schedule was completed during the third week of the study, creating a 3-h time in bed difference between the increase and decrease conditions. Sleep was monitored with actigraphy, and dietary intake was assessed with 24-hour dietary recalls. Participants reported consuming 35 kcal per day more from sugar-sweetened beverages during the decrease sleep than the increase sleep condition, p = .033. There were no reported differences between conditions from energy-dense snack foods. Although no differences in reported intake were observed earlier in the day, from 2000 h (8:00 PM) and later, children reported consuming 132 kcal more during the decrease sleep condition than the increase condition, p  < 0.001. Shortened sleep achieved by delaying bedtimes led to increased caloric intake in the evening and from sugar-sweetened beverages. Clinical Trials Registration: clinicaltrials.gov Identifier: NCT01030107 Highlights: When children sleep less caloric intake increases in the evening (2000 h and later). When children sleep less meal timing shifts to later in the day. Reported calories from sugar-sweetened beverages increase when children sleep less.